Towards Causal Datacenter Networks - Michael, Ellis; Ports, Dan R. K. (Proceedings of the 2018 Workshop on Principles and Practice of Consistency for Distributed Data (PaPoC '18), 2018)
Traditionally, distributed systems conservatively assume an asynchronous network. However, recent work on the co-design of networks and distributed systems has shown that stronger ordering properties are achievable in datacenter networks and yield performance improvements for the distributed systems they support. We build on that trend and ask whether it is possible for the datacenter network to order all messages in a protocol-agnostic way. This approach, which we call omnisequencing, would ensure causal delivery of all messages, making consistency a network-level guarantee.